Outcome of Neglected Elbow Dislocation Treated with Open Reduction at Rural Tertiary Care Hospital in Nepal - Rawal, Mangal; Rokaya, Poojan Kumar; Karki, Dhan Bahadur; Bhandari, Kailash Kumar; Thakur, Abhishek Kumar (Journal of Nepal Health Research Council, 2020)
Background: Chronic unreduced dislocation of elbow is a rare injury. Treatment options include open reduction internal fixation with K wire, replacement arthroplasty, excisional arthroplasty, arthrodesis, and hinged external fixator. The aim of this study is to determine the outcome of open reduction internal fixation with trans-olecranon K wire for neglected elbow dislocation.Methods: This is a retrospective study done in three rural hospital of Karnali. Hospital records were reviewed from July 2015 to May 2018 to identify 11 cases who underwent open reduction internal fixation for neglected elbow dislocation. Pre and Postoperative outcome was assessed using range of motion and Mayo Elbow Performance Index. Data analysis was done using SPSS version 17.Results: The average age of patient was 22.7 years (range 9-50 years). Non dominant hand was involved in 54.55%. The average preoperative elbow extension was 5.9 degree whereas postoperative extension was 15.9 degree. The average preoperative and postoperative elbow flexion was 24.5? and 113.6? respectively. Preoperative and postoperative Mayo elbow performance index was 18.6 and 86.3 respectively. Outcome was excellent in four patients, good in five patients and fair in two patients with one case having superficial infection.Conclusions: Open reduction and internal fixation with trans-olecranon k wire is an effective treatment method for neglected elbow dislocation. Postoperatively, elbow function is better with minimal complications.Keywords: Dislocation; elbow; neglected; open reduction